Electrical and optical of properties of nanostructured titanium dioxide (Ti02) thin film annealed at different temperatures / Mohd Azli Abdullah - Abdullah, Mohd Azli (2009)
Nanostructured titanium dioxide (TiO2) thin film has been synthesized using sol-gel method and deposited onto glass substrates using spin coating technique. These thin films then annealed at various temperatures. The electrical, optical and structural characterizations of the as deposited and annealed films were carried out using IV measurement with 4-point probe equipment, UV-Vis spectroscopy, atomic force microscopy (AFM) and scanning electron microscopy (SEM). From this study, it is known that, electrical properties were influenced by changes of annealing temperature. Resistivity of thin films was found to decrease as the annealing temperatures increase. Based on the readings from UV-Vis spectroscopy, it is found that transmittance properties of TiO2 thin films increased as annealing temperatures increase. This result is supported by surface topography and morphology of the thin films which indicate grains size increasing as temperature increases.